Impact of chronic opioid on cognitive function and spermatogenesis in rat: An experimental study - Hamid Norioun; Seyed Jamal Moshtaghian; Firoozeh Alavian; Maryam Khombi Shooshtari; Golnaz Alipour; Saeedeh Ghiasvand (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Opioid analgesics like morphine and methadone are widely used for managing severe pain; however, concerns over their potential misuse and adverse effects on the brain and reproductive system are significant. Objective: We aimed to investigate their impacts on spermatogenesis and cognitive function in male Norway rats. Materials and Methods: In this experimental study, 36 male Norway rats (250-300 gr, 6 months old) were divided into 6 groups: low-dose morphine, high-dose morphine, low-dose methadone, high-dose methadone, positive control (received normal saline at 5 mg/kg), and negative control (received no treatment). Morphine and methadone were administered intraperitoneally over 30 days at doses of 3 mg/kg and 7 mg/kg, respectively. Behavioral assessments evaluated anxiety, stress, and short- and long-term memory. Sperm parameters (viability, motility, morphology), hormonal analysis (testosterone, luteinizing hormone, follicle-stimulating hormone, estradiol), and gene expressions (Tp53, CatSper1) were assessed. Results: A significant reduction in rat weight was observed in the high-dose morphine group (p = 0.0045), while testicular weights remained unchanged. Sperm abnormalities were observed with high doses of methadone and morphine. High-dose methadone significantly reduced offspring count (p = 0.0004). Levels of follicle-stimulating hormone, luteinizing hormone, testosterone, and estradiol varied significantly across treatment groups. Gene expression was altered in response to treatments (p < 0.05). Conclusion: Prolonged exposure to methadone and morphine resulted in memory dysfunction, chronic stress, hormonal disturbances, altered gene expression, and fertility complications. These effects were more pronounced at higher doses, highlighting the importance of careful dosage management in opioid therapy.